Metode Antropometri Untuk Menilai Status Gizi : Sebuah Studi Literatur - Ratumanan, Samuel Permana; Achadiyani, Achadiyani; Khairani, Astrid Feinisa (Poltekkes Kemenkes Kendari, 2023)
Anthropometry is a science that quantitatively measures body composition. Anthropometry plays an important role in the health sector as a reference for diagnosis and clinical interventions, especially regarding nutritional status. Along with the times, anthropometric measurements are not only limited to conventional measurements (height, body mass index / BMI, etc.), but involve the latest advances in equipment and technology. Three-dimensional (3D) imaging is known to have precision and reliability comparable to conventional measurements, while DEXA is known to be the standard for bone density assessment. The writing method in this article is a literature review where the articles taken will be screened for relevance by reading the title and abstract. The results of the analysis of this study indicate that the use of the latest methods such as 3D imaging and DEXA is known to have similar results when compared to conventional measurements. The conclusion of this study is that 3D imaging is known to be precise and reliable so that it can be used for anthropometric examinations, while the DEXA method has been recognized as the gold standard in assessing bone density.